Measurement of Microfibril Angle Using X-Ray Diffraction and Light Microscope on 5-year-old Super and Conventional Teak Wood - Setiowati Setiowati; Ratih Damayanti; I. Ketut N. Pandit; Fauzi Febrianto; Gustan Pari (Wood Research Journal, 2014)
The long   harvest time  causes the   processing  industry  manufactured  from   teak  wood (Tectona  grandis L.  f.)  has experienced  a lot of declines. To overcome this  problem,  currently,  in Indonesia  many types  of fast-growing  teak  have been developed, one of which is Jati Unggul Nusantara (JUN). Trees that  are accelerated in growth, are likely to cause changes in their  anatomical  structure. The anatomical  structure of wood is one of the  basic  properties  that  greatly influences  the  use of wood as a raw  material. Even small changes in cell shape and size can change the  properties of wood as a raw  material. One of the  anatomical  structures of wood, namely the  ultramicroscopic  structure that  affects the  quality  of wood, is the  microfibril angle (MFA). The purpose of this  study is to determine  the  MFA of JUN at the  planned cutting  age of 5 years, compared to conventional teak at  the  same age. There are two  methods used, namely using X-Ray Diffraction (XRD) and measuring the elongation  of  the  pit  apertures slope of  the  fiber  cells using  a light  microscope,  which was obtained from  the  maceration process. As  a result, JUN's MFA is 22.09°, smaller than  the  conventional teak of 25.29°. This is because JUN was developed from  top  cuttings  so  although  still  young, it  already  reflects  the   characteristics  of  mature teak. The results of  the  MFA measurements on  JUN using two  methods (XRD and light microscope), resulted different values. It is different from  the  MFA measurement results on  conventional teak. It is recommended to  measure the MFA in JUN wood by  using XRD, because possibly, due to accelerated  growth, simple pits with an  oval shape turn  into circular. This difference causes the  results of the JUN MFA measurement using a light microscope based on the  pit apertures slope to be  inconsistent, subjective, and different results  in  other  pits   contained  in  the   fiber   even  though they  are  closely  associated. However,  in  conventional  teak, measurements using a light microscope are possible because the  shape of the  pit is oval so  that  the  slope of the  elongation of the  pit aperture can be  determined easily, and is more consistent with more uniform values in the  same individual fiber